Introduction - Barney G. Glaser (Grounded Theory Review: An International Journal, 2013)
Memos are neglected as a GT procedure. Memos are where the emergent concepts and theoretical ideas are generated and stored when doing GT analysis. They are a neglected procedure mostly in writing about doing GT, yet they are vital to GT analysis for recording ideas, saving and tracing growth of analysis and integrating GT concepts as they emerge from constant comparative analysis during open coding and selective coding when theoretically sampling. Memos track the generation of a substantive GT from start to working paper.